Interactions with heterospecific males do not affect how female Mesocricetus hamsters respond to conspecific males - delBarco-Trillo, Javier; Johnston, Robert E. (Animal behaviour, 2013)
Reproductive interference includes any interspecific interaction that reduces the fitness of one or both species involved. There are several types of reproductive interference, but they normally involve the direct cost of interacting or mating with heterospecifics. An indirect cost of interacting with heterospecific individuals is a consequent reduction in successful interactions with conspecifics. We tested the hypothesis that being aggressive towards a heterospecific individual will diminish sexual responses towards conspecifics in later encounters. We used two species of Mesocricetus hamsters (Syrian and Turkish hamsters), whose interspecific interactions have previously been determined. We exposed or both exposed and paired Syrian hamster females with a conspecific or a heterospecific male. Five minutes later, we paired all females with a conspecific male and measured the latency to lordosis, the duration of lordosis and any incidence of aggression. We found that (1) interactions with heterospecific males did not affect how females responded to conspecific males in later encounters and (2) previous pairing of female subjects with either conspecific or heterospecific males promoted a faster sexual response by females in subsequent interactions with conspecific males. Thus, aggressive interactions of Syrian hamster females with heterospecific males, contrary to our initial hypothesis, had a positive effect on subsequent interactions with conspecific males. ► Female interactions with a heterospecific male do not affect conspecific behaviour. ► Across treatments, females were not aggressive towards conspecific males. ► Pairing with any male type promotes faster sexual response with conspecific males.